Influence of supplemental choline on milk yield, fatty acid profile, and weight changes in postpartum ewes and their offspring - María M. Crosby-Galvan; German D. Mendoza; Pedro A. Hernández-García; José Antonio Martínez-García; Anayeli Vázquez-Valladolid; Rubén Oswaldo Cifuentes-López; Héctor A. Lee-Rangel (Veterinary World, 2024)
Background and Aim: The most intensive nutritional requirements occur during milk production’s peak. Ewe milk contains more protein and fat than cow milk. The nutritional factors significantly determine the composition. The liver undergoes high stress during lactation but is relieved by essential nutrients. Choline acts metabolically as a lipotrope. This compound functions in cell structure construction, maintenance, and acetylcholine synthesis. The animal nutrition industry provides choline from various sources, such as synthetic and natural kinds. This study evaluated the influence of two distinct choline sources on dairy ewes’ peripartum and postpartum milk production, composition, and offspring growth.